IMPLEMENTASI METODE UMMI DALAM PEMBELAJARAN TAHFIDZ DI SD IT RABBI RADHIYYA 02 CURUP REJANG LEBONG - Ahmad Ridwan; Hilda Dwifa; M. Ikram; Yuhendri Gusman (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Tahfidz or memorization is pronunciation that is done repeatedly and is a teaching that is done for the first time orally or by memorization. By memorizing you need to use methods to make it easy and fun, such as applying the Ummi method. The ummi method is a practical Qur'an reading method that does not require much explanation and is repeated in learning to read the Qur'an. This method uses tones or songs that can make it easier for students to memorize. SDIT Rabbi Radhiyya is one of the schools that implements tahfidz learning using the ummi method and has been implemented for 1 year and progress has been seen. This research focuses on tahfidz learning in class V of SDIT Rabbi Radhiyya. The problems formulated in this research are (1) How is the implementation of the ummi method at SDIT Rabbi Radhiyya 02 (2) What are the supporting and inhibiting factors in implementing the ummi method at SDIT Rabbi Radhiyya 02. This research aims to determine the implementation of the Ummi method in learning tahfidz at SDIT Rabbi Radhiyya 02 as well as the supporting and inhibiting factors. This research uses a type of field research using a qualitative approach. The data sources obtained came from primary data and secondary data. This research uses data collection techniques, namely observation, interviews and documentation. The results of this research show that the implementation of the ummi method in learning tahfidz uses tones or songs in each lesson, be it tahsin or tahfidz. Preparations can be made in the form of classrooms, dividing groups to take part in this tahfidz learning with a fun implementation. Its implementation uses several steps, namely Opening, Appreciation, Concept Planting, Concept Understanding, Practice/Skills, Assessment/evaluation, and Closing. The evaluation results of student assessments have increased successfully using this method and many students have achieved the targets set by the school. Supporting factors in implementing the Ummi method are having adequate facilities and creativity for teachers, potential students, and families who support learning conditions. Meanwhile, the inhibiting factors are the different abilities of students, families who do not support them, and the quality of each student's reading. Keywords: Tahfidz Learning, Ummi Method, SDIT Rabbi Radhiyya 02